2020
DOI: 10.1111/jopr.13148
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tooth Preparation Design and Scan Angulations on the Accuracy of Two Intraoral Digital Scanners: An in Vitro Study Based on 3‐Dimensional Comparisons

Abstract: Purpose To evaluate the accuracy of two intraoral scanners (IOS) in terms of different preparation designs and scan angulation limitation due to the presence of adjacent teeth. Materials and Methods Eight different complete coverage (CC) and partial coverage (PC) tooth preparations were scanned by two IOS, the 3Shape TRIOS (TRI) and the 3M True Definition (TRU). All teeth preparations were scanned in the presence and absence of adjacent teeth. Four groups were established for each IOS; Group 1: PC preparations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 28 publications
(54 reference statements)
0
39
0
5
Order By: Relevance
“…The discrepancy may come from the intraoral conditions of the patient which influence the accessibility of the scanners during the scanning phase. The importance of its accessibility was confirmed by a recent study which showed that partial coverage preparation and the presence of adjacent teeth resulted in significantly less accuracy due to the limitation of scan angulation and direction [25].…”
Section: Discussionmentioning
confidence: 98%
“…The discrepancy may come from the intraoral conditions of the patient which influence the accessibility of the scanners during the scanning phase. The importance of its accessibility was confirmed by a recent study which showed that partial coverage preparation and the presence of adjacent teeth resulted in significantly less accuracy due to the limitation of scan angulation and direction [25].…”
Section: Discussionmentioning
confidence: 98%
“…The four software programs used in this study were used as evaluation tools for the accuracy of the 3D scanner in previous studies [2,6,15,16]. Of the four software programs, Geomagic control X has been used in most studies [3,14,26]. Materialise 3-matic is a 3D modeling software, and the 3D analysis applied in this study is an additional function of the software.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have proposed a method to evaluate the accuracy of an intraoral or desktop scanner [1][2][3][4][6][7][8]10,11,[14][15][16]. The accuracy of the virtual cast was evaluated by measuring the linear distance between specific oral structures or between teeth of dental arches [8,17].…”
Section: Introductionmentioning
confidence: 99%
“…Ayrıca inley,onley gibi negatif yüzeylerde ayrıntıların daha az çıktığı görülmüştür. 81 Tablo 2, 3'deki veriler değerlendirildiğinde; intraoral tarayıcılar arasında Trios 3'ün hem daha başarılı sonuçlar verdiği hem de çalışmalarda daha çok tercih edildiği görülmüştür. 26,50,51,[82][83][84] Buna ek olarak bazı çalışmalarda CS 3600, True Definition ve Element 1 tarayıcıları kısa alan taramalarında tatmin edici değerler vermiştir.…”
Section: Tam Ark Taramaunclassified